Role of Ultrasound in the Diagnosis of Non-Alcoholic Fatty Liver Disease (NAFLD) - Abdul Salam, Ayesha Malik, Nadir Farid, Mehwish Lali, Muhammad Imran Farid, Abdul Wadood, Sani Gawhar, Sobia Wali Muhammad, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The most prevalent liver illness, nonalcoholic fatty liver disease (NAFLD), is characterized by abnormal fat buildup in the hepatocytes without a substantial alcohol consumption history or secondary causes of fatty liver disease. Aim: This study aims to assess ultrasound's diagnostic utility in NAFLD. Material and Method: In the Hayatabad Medical Complex (HMC) in Peshawar, Pakistan, a cross sectional study with convenient sampling technique was conducted over six-month. This study received permission from the Institutional Research and Ethical Review Board (IREB) of HMC Hospital, and Open-Epi determined the sample size of 250 patients with a 95% confidence interval and a 5% margin of error. A certified sinologist conducted the abdominal ultrasound. The right arm was extended to its maximum abduction while the participants were positioned in the dorsal decubitus position. Using a right intercostal technique, the right liver lobe was seen, and a representative parenchymal region was identified without compromising the main vascular. The data were gathered through Questionnaire and analyzed using SPSS version 26. Results: There were 250 participants, with 55.4% men and 44.2% women. Patients between 40 and 49 accounted for 38.4% of the affected population. The most common conditions among patients with NAFLD were mild severity (49%) and abdominal discomfort (47.4%). Only (8%) of participants had liver cirrhosis before NAFLD while (91.6%) of patients lacked liver cirrhosis before NAFLD. When treating suspected NAFLD, 83.3 percent of patients preferred the Ultrasound modality initially, and more patients received a primary ultrasound diagnosis. Practical Implication: Ultrasound is the most commonly used modality because of their availability and low cost but its role in NAFLD is not fully diagnosed and evaluated. This study aims to evaluate the proper use of the Ultrasound modality in NAFLD for the benefits of patients to be diagnosed initially with Ultrasound so that it may not lead to a serious problem. Conclusion: A valuable non-invasive imaging technique for the diagnosis of non-alcoholic fatty liver disease (NAFLD) is ultrasound. Most patients first favor ultrasound, which is considered the leading imaging modality for NAFLD suspicion. The majority of NAFLD patients were middle-aged and male. Keywords: Abdominal pain, Fatigue, Liver cirrhosis, Non- Alcoholic Fatty Liver Disease, Ultrasound